The Leptin Concentration Level in Progression of Hand Osteoarthritis Disease - Maryam Qais Ahmed; Ghaith Sael Mohammed (Indian Journal of Forensic Medicine & Toxicology, 2021)
Subject :Hand Osteoarthritis (HOA) is know as degenerative cartilage cell disease in joint association withgeneration various inflammatory responses . This disease is more common in geriatric and effected bymany factors such as obesity . Leptin is hormones secreted of fatty tissue involve as mediators in manypathophysiology process , and support inflammation at cartilage of hand joint .Objective of the Study: Role of leptin concentration level in progression of hand Osteoarthritis .Materials and Methods: This study was done on 60 patients with HOA disease and 60 healthy persons(control ), the all subjects age within this study were more than 60 years of both genders .After obtainedserum , immediately used quantity method (immunoassay) for measured level of leptin concentration .Results: This study shows elevation of serum leptin concentration level in HOA group compare with healthycontrol group .Conclusion: This study confirms that serum leptin concentration level can act as support HOA diseaseprogression .